Colonic diverticula - Płachecka, Ewa (Nursing in the 21st Century, 2013)
COLONIC DIVERTICULAColonic diverticulum is a mucosa enterocyte which protruding into the muscle wall of the intestine leads to anatomic and functional changes in the digestive tract. It mostly affects elderly people. Diverticula frequently occur in the left part of the colon. They never penetrate bands and are usually located between the mesenteric and opposite bands, of ten appearing in symmetrically placed pairs. The size of diverticulum ranges from a slight bulge of the estrous membrane to hanging sacs that are 2cm long and dark translucent due to the presence of stool. The sites of diverticulum protrusion correspond to the places of penetration of blood vessels through the intestinal wall. Usually, a few diverticula bleed at the same time. Bleeding intensity varies as bleeding can be detected only via laboratory tests or can be well visible in the stool. Diverticula may appear along the entire length of the colon, although they are most frequently observed in the segment of the sigmoid colon (70-90%). Moreover, right sided diverticular disease may also occur but only in 14% of cases. Diverticula can be single or multiple.